Japanese Military Government Policy on Radio Broadcasting in Java - Budiarto, Gema; Yuliati, Dewi; Puguh, Dhanang Respati (Universitas Airlangga, 2024)
In World War II, radio was one of the effective communication media that could be used to spread news and propaganda. The Japanese military government in Java made efforts to control or censor radios owned by the public. Control and censorship efforts to prevent the public from listening to radio broadcast by the Allies. On the other hand, radio was also useful for Japan to spread propaganda in society. The purpose of this study is to examine the policy of the Japanese military government in controlling and utilizing radio as a propaganda media in Java during wartime. This study is a historical research, thus the method used in this study is the historical method. The primary data used were Asia Raya newspaper, Djawa Baroe magazine, and Kan Pō (the government news) published by the Japanese military government in Java in 1942-1945. The results of this study show that the Japanese military government paid great attention to radio broadcasting and was strict in controlling it, radio broadcasts from enemy countries (Allies) were strictly forbidden to be listened to by the public, even the Japanese military government will impose severe punishment on the people if anyone violates. However, the Japanese military government also employed radio as a media for disseminating propaganda such as radio speeches from Japanese military officials, government programs, news, and so on.